In vitro Activity of Esomeprazole Against Ureaplasma Species. (4th October 2017) - Wi, Yu Mi; Greenwood-Quaintance, Kerryl; Karau, Melissa J; Patel, Robin
Abstract: Background: Hyperammonemia syndrome affects up to 4% of lung transplant recipients, and has recently been shown to be caused by Ureaplasma ureallyticum or Ureaplasma parvum . Since proton-pump inhibitors (PPIs) are used in the management of another urease-producing organism, Helicobacter pylori, we evaluated the activity of a PPI, esomeprazole, against Ureaplasma species. Methods: Esomeprazole (EPZ) minimum inhibitory concentrations were determined according to CLSI guidelines using U. parvum ATCC 27815, and two clinical isolates, U. urealyticum IDRL-11264 and U. parvum IDRL-10763. The EPZ MIC of all three isolates was 256 µg/mL. Time-kill assays were performed using concentrations of 0.5X and 1X the MIC of EPZ, and a growth control without EPZ. The tested strains were prepared by growing them in 10B broth with a final inoculum of approximately 2 × 10 6 CFU/mL. Bacterial quantity and pH were measured every 3 hours over a 24 hour period of incubation at 37°C. Results: Time kill curves obtained from growth controls were the same as those obtained with half MICs of EPZ. Time kill curves of 1× MIC of EPZ and growth controls are shown in Figures 1 and 2. Figure 1 demonstrates pH changes over time. All Ureaplasma isolates had a smaller increase of pH with as compared with without EPZ exposure. Time kill curves, shown in Figure 2, demonstrate viability at later time points with exposure to EPZ compared with no exposure to EPZ for all strains tested. Conclusion: Exposure to EPZ under the conditions studied enabled longer survival of Ureaplasma species as well as lower pH. Further evaluation is needed to understand the effects that PPIs may have, if any, on Ureaplasma infections. Disclosures: R. Patel, ASM: Board Member, None. CD Diagnostics, BioFire, Curetis, Merck, Hutchison Biofilm Medical Solutions, Accelerate Diagnostics, Allergan, and The Medicines Company: Grant Investigator, Grant recipient. Curetis: Consultant, Monies paid to my employer. A patent on Bordetella pertussis/parapertussis PCR issued, a patent on a device/method for sonication with royalties paid by Samsung to Mayo Clinic, and a patent on an anti-biofilm substance issued: Patents, Patents, any money is paid to my employer. Actelion: DSMB, Money paid to my employer. ASM and IDSA: Editor's stipends, Editor's stipends. NBME, Up-to-Date and the Infectious Diseases Board Review Course: NBME, Up-to-Date and the Infectious Diseases Board Review Course, Honoraria